Analysis of the Al-Islam and Kemuhammadiyahan Curriculum Design - Nurman Ginting; Amini Amini; Faizal Lubis (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the implementation of the Al-Islam and Kemuhammadiyahan (AIK) curriculum at SMP Muhammadiyah 01 Medan, focusing on its relevance, pedagogical practices, assessment systems, and supporting institutional factors. Using a qualitative case-study design, data were collected through interviews, classroom observations, and document analysis involving teachers, students, parents, and school documents. The findings reveal that the AIK curriculum is perceived as normatively strong, emphasising akhlaq, ibadah, and Qur’anic understanding, yet remains limited in addressing contemporary issues, particularly digital ethics and media-literacy challenges commonly experienced by adolescents. Classroom practices were dominated by lecture-based instruction, although discussion and project-based learning were present in several sessions. Parental involvement in religious activities was relatively high, but communication regarding students’ behavioural development was inconsistent. Assessment practices largely relied on written examinations, with minimal use of authentic or performance-based evaluations. Structural constraints including outdated textbooks, limited teacher professional development, and low technological integration, further hindered optimal curriculum enactment. Overall, the study concludes that while the AIK curriculum provides a solid normative foundation, its effectiveness is constrained by pedagogical, structural, and contextual limitations. The study recommends enriching the curriculum with contemporary Islamic digital-ethics content, strengthening teachers’ capacities in student-centred and technology-supported pedagogies, improving communication systems with parents, and expanding authentic assessment methods. These improvements are expected to enhance the curriculum’s relevance and its capacity to cultivate holistic Islamic character development aligned with the demands of the digital era.